OPTIMALIASI PELAKSANAAN PEMBERIAN BANTUAN HUKUM BAGI TERSANGKA TINDAK PIDANA NARKOTIKA - Sahabat, Andi Inar (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM IBLAM), 2023)
This research aims to find out how optimal the implementation of providing legal assistance is for suspects of narcotics crimes. This research uses empirical research methods, namely research based on empirical fact data in the field such as the results of interviews and observations taken directly from observations made by researchers in the field. The results of the research show that the implementation of providing legal assistance by investigators and legal advisors to explain narcotics crimes has been very effective or in accordance with procedures based on law. However, in providing legal assistance there are still obstacles that hinder the provision of legal assistance, namely the refusal of suspects who do not want to be accompanied by legal advisors due to a lack of understanding regarding legal assistance and also other obstacles, namely SKM or poverty certificates which are very difficult to obtain from the sub-district/village. This causes the provision of legal aid to be less than optimal.